Intubating laryngeal tube suction device (iLTS-D) requires 'Mandheeral 1 and Mandheeral 2' manoeuvres for optimum ventilation. (4th March 2018) - Singh, Manpreet; Kapoor, Dheeraj; Anand, Lakesh; Sharma, Ankit
Abstract : The recently introduced iLTS -D ® combines the characteristics of laryngeal tube suction-D with the added possibility of secondary tracheal intubation. The manufacturer has provided a method to insert the novel device, iLTS-D. With 45-patients worth of experience, two manoeuvres, i.e. Mandheeral 1 and Mandheeral 2, are recommended for smooth insertion of the device, and ventilation through the device. These were head extension and 'up-to-one-inch-out manoeuvres'. These two manoeuvres were required in all patients.